Beyond Purchasing Decisions: Consumer Behavior in Students’ Part-Time Work Decisions and Consequences - Farida Tri Hastuti; Priyanto; Heryanto, Erie Irawan (JURNAL MANAJEMEN MOTIVASI, 2026)
Consumer behavior generally focuses on purchasing decisions, while its application to non-purchase decisions remains limited. This study examines the impact of the Part-Time Work Decision (PTWD) on Job Satisfaction (JF) and Job Stress (JS) among students working part-time. Purposive sampling selected 119 respondents, and data were analyzed using PLS-SEM with SmartPLS 4. The findings show that PTWD significantly affects JF (β = 0,418; t = 5,499; p < 0,000), whereas PTWD has no significant effect on JS (β = -0,065; t = 0,473; p = 0,697). This study extends the consumer decision process to non-purchase decisions